Paciente con leucemia linfoblastica aguda - Ycaza Guayalema, Ariana Maria (2018)
Blood cancer affects white blood cells. Leukemia is the most common cancer in children and adolescents. These cells are formed in the bone marrow. The white blood cells are responsible for fighting the infectious processes in our body, when the individual is ill with cancer to the blood responsible for forming blood cells, produces abnormal white blood cells and these replace normal cells and do not let them comply its function normally. The standard maintenance method involves the administration of mercaptopurine daily and weekly methotrexate. Users attend the treatment on an outpatient basis, attending their controls every 2-4 weeks. During the same they receive anti-infective prophylaxis with cotrimoxazole three days a week. They can attend school and carry out their normal daily life. The interest of this case study arose from seeing the high numbers of cancer cases in the blood which is a potential health problem because it threatens life. This problem manifests itself most frequently in children and adolescents. When the person who suffers it is a child which also involves the family mainly the parents who are responsible for their care. After making the corresponding assessment they decide to request laboratory tests: blood count, biochemical tests, blood cell reunion, bone marrow aspiration and biopsy, lumbar puncture, when these studies were diagnosed, acute lymphoblastic leukemia was diagnosed, reason why the patient was left hospitalized. patient, to receive treatment with chemotherapy.